Sweden and ecological governance: Straddling the fence - Lundqvist, Lennart J. (Manchester University Press, 2004)
Sweden is seen as a forerunner in environmental and ecological policy. Sweden and ecological governance is about policies and strategies for ecologically rational governance, and uses the Swedish case study to ask whether or not it is possible to move from a traditional environmental policy to a broad, integrated pursuit of sustainable development, as illustrated through the 'Sustainable Sweden' programme. The study begins by looking at the spatial dimensions of ecological governance, and goes on to consider the integration and effectiveness of sustainable development policies. It analyses the tension between democracy and sustainable development, which has a broader relevance beyond the Swedish model, to other nation states as well as the European Union as a whole. In this book the author offers the latest word in advanced implementation of sustainable development by a front-runner in environmental and ecological policy. It will be useful for students of environmental politics and sustainable development researchers.